Essential Oils from Leaves of Virola calophylla, Virola multinervia, and Virola pavonis (Myristicaceae): Chemical Composition and Larvicidal Activity against Aedes aegypti. Issue 3 (3rd May 2020) - Mesquita, Rochelly da S.; de Oliveira, André C.; Sá, Ingrity S.C.; Sales, Maiara L.F.; Bastos, Lilian M.; Koolen, Hector H.F.; Tadei, Wanderli P.; da Silva, Felipe M.A.; Nunomura, Rita C.S.
Abstract: Essential oils (EOs) from leaves of Virola calophylla, Virola multinervia, and Virola pavonis (Myristicaceae) were obtained by hydrodistillation, analyzed by gas chromatography coupled with mass spectrometry (GC/MS), and investigated for their larvicidal activity against Aedes aegypti larvae. The major compounds identified in the EOs were β-caryophyllene (54.8 % in V. calophylla and 55.7 % in V. multinervia) and β-selinene (60.5 % in V. pavonis ) . The EOs showed low larvicidal activity, LC50 =179.6 μg/mL for the V. calophylla EO, followed by those of the V. pavonis LC50 = 185.1 μg/mL and V. multinervia LC50 = 200.5 μg/mL. The β-selinene-rich fraction (78.6 %) isolated from V. pavonis EO showed no larvicidal activity (LC50 > 350 μg/ mL). These results represent the first report about the chemical composition and the larvicidal evaluation of the EOs from those Amazonian Virola species.